Production and Reception of Iranian Feminist Cinema: "The Unwanted Woman" - Sadeghian, Negar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This study brings together the work of Tahmineh Milani, known for directing Iran's highest-grossing film and for winning international awards. In her career, she stands out for her political treatment, having had problems with censorship, and for being the first imprisoned filmmaker in the country's history. This is why this research aims to analyze the repercussion of Milani's work, from the point of view of its production and reception. In this respect, historical documents serve to contextualize the cinematographic activity of the filmmaker and the analysis of her work.